Atomic Layer Deposition Derived Zirconia Coatings on Ni‐Rich Cathodes in Solid‐State Batteries: Correlation Between Surface Constitution and Cycling Performance. Issue 2 (11th December 2022) - Kitsche, David; Tang, Yushu; Hemmelmann, Hendrik; Walther, Felix; Bianchini, Matteo; Kondrakov, Aleksandr; Janek, Jürgen; Brezesinski, Torsten
Abstract : Protective coatings are required to address interfacial incompatibility issues in composite cathodes made from Ni‐rich layered oxides and lithium thiophosphate solid electrolytes (SEs), one of the most promising combinations of materials for high energy and power density solid‐state battery (SSB) applications. Herein, the preparation of conformal ZrO2 nanocoatings on a LiNi0.85 Co0.10 Mn0.05 O2 (NCM85) cathode‐active material (CAM) by atomic layer deposition (ALD) is reported and the structural and chemical evolution of the modified NCM85 upon heat treatment—a post‐processing step often required to boost battery performance—is investigated. The coating properties are shown to have a strong effect on the cyclability of high‐loading SSB cells. After mild annealing (≈400 °C), the CAM delivers high specific capacities (≈200 mAh g −1 at C/10) and exhibits improved rate capability (≈125 mAh g −1 at 1C) and stability (≈78% capacity retention after 200 cycles at 0.5C), enabled by effective surface passivation. In contrast, annealing temperatures above 500 °C lead to the formation of an insulating interphase that negatively affects the cycling performance. The results of this study demonstrate that the preparation conditions for a given SE/CAM combination need to be tailored carefully and ALD is a powerful surface‐engineering technique toward this goal. Abstract : The secondary particles of the cathode material LiNi0.85 Co0.10 Mn0.05 O2 are conformally coated with ZrO2 nanoshells making use of the unique capabilities of atomic layer deposition (ALD). The multifaceted evolution of the surface structure upon post‐heat treatment and its effect on the cycling performance of thiophosphate‐based solid‐state batteries are studied systematically.